Keberadaan Mikoriza Arbuskular pada Lokasi Pertanaman Jarak Pagar (Jatropha curcas L.) di Lembah Palu - Iskandar Lapanjang (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
Plant rhizosphere has various types of microorganisms, including Arbuscular Mycorrhizae Fungi (AMF). Each ecosystem has different species and densities of AMF. For further use, study the potency of indigenous AMF is necessary. This research was conducted to know the existence and potency of indigenous AMF of soil where physic nuts grow on dry land of Palu Valley at Poboya, Palu, Central Sulawesi. Soil samples were collected, and then observed under microscope. The steps to study the potency of AMF were counting the propagules with Most Probable Number (MPN) method, spora trapping, identifying the types of spore, and single spore culture. The result showed that the number of infective AMF propagules from cultivated soil was 1117 microorganisms/g soil and from of natural soil was 711 microorganisms/g soil; and indigenous AMF from the soil where physic nut grown at Lembah Palu were dominated by Glomus sp.